Budidaya Hidroponik sebagai Upaya Pemberdayaan Kelompok Wanita Tani Citra Mandiri Desa Parangjoro - Lalita Paramastri; Larasati Widya Nugraheni; Fathin Abdullah Basyir; Kalis Jalu Pamungkas; Kalya Shakti Effendie; Keisya Alifya; Kholillah Shofiy Insyiroh; Lambang Ilham Dwi Syahputra; Lintang Sindu Larasati (PRIMA: Journal of Community Empowering and Services, 2026)
Hydroponic Cultivation as an Empowerment Effort for The Citra Mandiri Women Farmers Group in Parangjoro Village. Women's empowerment in the agricultural sector is hampered by limited access to capital and technology. Parangjoro Village has an organization, the Citra Mandiri Women's Farmers Group (KWT), which plays an active role and is oriented towards economic independence. Efforts to support the activities of KWT Citra Mandiri require sustainable economic activities that will bolster members' incomes. Hydroponic cultivation was chosen as an alternative measure due to limited land and the implementation of government programs, namely food security. Hydroponic cultivation practices aim to introduce and demonstrate hydroponic plant cultivation, increase the knowledge and skills of KWT Citra Mandiri members, and open economic opportunities through appropriate marketing strategies, especially in the digital marketing sphere, so that hydroponic results can increase the economic independence and welfare of KWT Citra Mandiri members. Through the participatory rural appraisal (PRA) and asset-based community development (ABCD) approaches, KWT Citra Mandiri members can be directly involved in the process of analyzing problems and developing independent solution plans, focusing on utilizing assets and potential in Parangjoro Village to support sustainable agriculture. This method encourages KWT Citra Mandiri members to play an active role in the planning, implementation, and evaluation of hydroponic cultivation. The implementation results showed that each stage of hydroponic cultivation provided a comprehensive understanding of the basic principles of hydroponics, maintenance techniques, and handling of technical obstacles. The Citra Mandiri KWT utilized digital e-commerce platforms, social media, and direct marketing to expand market reach. The final evaluation showed that the hydroponic cultivation outreach program attracted 50% of participants' interest in applying hydroponic cultivation, thus potentially improving the economic well-being of the Citra Mandiri KWT.